Thismia puberula (Thismiaceae), a new species from Southern Vietnam - Nuraliev, Maxim; Beer, Anton; Kuznetsov, Andrey; Kuznetsova, Svetlana (Phytotaxa, 2015)
Thismia puberula, a new species of Thismiaceae, is described and illustrated. The species was discovered in 2014 during botanical survey of Chu Yang Sin national park (Dak Lak province, Southern Vietnam). Thismia puberula possesses vermiform roots and mitriform inner tepals. It is most similar to T. angustimitra, T. mirabilis, T. mucronata and T. okhaensis. The new species differs from related species mainly by dome-shaped annulus with delimited vertical and horizontal parts covered by hairs, broad mitre with foveae, inner mitre surface covered by papillate trichomes, and presence of interstaminal glands. An updated key to Vietnamese species of Thismia is provided.